Kombinasi Algoritma Kriptografi Vigenere Cipher dan SHA256 untuk Keamanan Basis Data - Rian Oktafiani; Erik Iman Heri Ujianto; Rianto Rianto (Universitas Budi Darma, 2023)
An organization must consider and manage the security of data storage in databases or databases, and special procedures are needed to protect data from various security risks. The problem in this study is that the population data contained in the Girisuko village administrative service information system has not been encrypted or secured. This can pose a risk that the data stored in the database can be intercepted and misused. In this study, the cryptographic technique used was a combination of the Vigenere Cipher and SHA 256 algorithms to secure or encrypt databases, especially population data in the Girisuko village administrative service information system. The text in the database is encrypted using the Vigenere Cipher, and SHA-256 is used to generate a hash value or a random value that is different from the text in the database. Messages will be encrypted using the Vigenere Cipher and then hashed with SHA-256 simultaneously. As a result, it will be difficult for an attacker to decrypt the text stored in the database because they have to break the Vigenere Cipher encryption, and also have to solve the hash value generated using SHA-256. This combination aims to increase security and maintain the confidentiality of messages from attackers. The application of the Vigenere Cipher and SHA to the village administration service information system application with a real-time database works well, as evidenced by the fast running-time of 0.39 seconds the data encryption process uses the Vigenere Cipher with 894,968 keys/second and an analyzed key length of 7 characters then text on population database successfully secured. By conducting this research, it is hoped that it can contribute to improving database system security.